2010
DOI: 10.1159/000321725
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Pulmonary Dendritic Cells and Th2-Type Inflammatory Responses on Instillation of Engineered, Environmental Diesel Emission Source or Ambient Air Pollutant Particles in vivo

Abstract: The biological effects of acute particulate air pollution exposure in host innate immunity remain obscure and have relied largely on in vitro models. We hypothesized that single acute exposure to ambient or engineered particulate matter (PM) in the absence of other secondary stimuli would activate lung dendritic cells (DC) in vivo and provide information on the early immunological events of PM exposure and DC activation in a mouse model naïve to prior PM exposure. Activation of purified lung DC was studied fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 116 publications
2
52
0
2
Order By: Relevance
“…The activated dendritic cells selectively provoked a Th2-biased immune activation of allogeneic CD4 + T cells. 136 Although engineered nanoparticles (carbon black and silver nanoparticles) were not shown to cause similar responses in the same investigation, the involvement of nanoparticles in the observed immunological effects cannot be excluded. Oral or peritoneal exposure of mice to polyethylene glycol-coated poly-DL-lactic-co-glycolic acid (PLGA) nanoparticles induced immune reactions.…”
Section: Immunotoxicitymentioning
confidence: 89%
“…The activated dendritic cells selectively provoked a Th2-biased immune activation of allogeneic CD4 + T cells. 136 Although engineered nanoparticles (carbon black and silver nanoparticles) were not shown to cause similar responses in the same investigation, the involvement of nanoparticles in the observed immunological effects cannot be excluded. Oral or peritoneal exposure of mice to polyethylene glycol-coated poly-DL-lactic-co-glycolic acid (PLGA) nanoparticles induced immune reactions.…”
Section: Immunotoxicitymentioning
confidence: 89%
“…The effect was not observed in the AgNP-treated and OVA-sensitized mice. Previous studies have established that AgNP are causative agents of asthma development, 33,34 and the disease could be attributed to inflammatory responses. Indeed, our findings also suggested that the exposure of healthy mice to AgNP resulted in an increase in inflammatory reactions (ie, interstitial lymphocytic and neutrophilic inflammatory infiltration in the lungs).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidant stress seems to be involved in diesel-associated increases in allergic inflammation and airway hyperresponsiveness as evidenced by experiments in Nrf2 knockout mice (19) and exposure of dendritic cells (DC) to diesel exhaust particle extracts (20,21). Ambient and diesel particulates instilled into the oropharynx have been shown to activate pulmonary DC and promote eosinophilia and Th2-type responses in mice (22). In a study comparing responses to several chemically distinct preparations of diesel exhaust particles, potentiation of murine allergic immune responses seemed to correlate with diesel exhaust content of polycyclic aromatic hydrocarbons (23).…”
Section: Discussionmentioning
confidence: 99%